Does the pain sensitivity questionnaire correlate with tourniquet pain in patients undergoing ankle surgery? - Fu, Qiuyue; Han, Mingming; Mu, Yuyang; Hao, Lina; Lu, Liang; Huang, Xiang; Li, Juan; Kang, Fang (Frontiers in Surgery, 2023)
Abstract Background: Tourniquet pain is the most prominent problem in ankle surgery, and there is no proper method to predict it. It was reported that pain sensitivity questionnaires could evaluate the pain sensitivity of subjects. Its potential to predict tourniquet pain in ankle surgery is constructive and meaningful. Methods: One hundred and twenty patients undergoing ankle surgery were included in this study. The pain sensitivity questionnaire (PSQ) and self-rating Anxiety Scale (SAS) were completed before the operation. The methods included an ultrasound-guided popliteal sciatic, femoral nerve block, and a proximal thigh tourniquet. The pressure of the tourniquet was set according to systolic blood pressure (SBP + 100 mmHg). A visual analogue scale (VAS) was used to assess the tourniquet pain. And the onset time of tourniquet pain ≥4 VAS units was recorded. Results: The PSQ-total and PSQ-minor score was significantly correlated with the onset time when the tourniquet pain ≥ 4 VAS units (r=－0.763, r=－0.731, P<0.001). The group of PSQ-total score ＜ 6.5 gave significantly lower ratings for items 3, 4, 14, and 16 in the PSQ survey, compared to the group of PSQ-total score ≥ 6.5 (P<0.05). Patients with high pain sensitivity have a higher need for analgesic drugs (P<0.001). PSQ-total score ≥6.5 (OR=185.8, 95%CI=39.8-1437.6, P<0.001), sex (male, OR=0.11, 95%CI=0.018-0.488, P<0.05) and age (OR=0.92, 95%CI=0.842-0.995, P<0.05) were risk factors of reporting a tourniquet pain ≥4 VAS units within 30 minutes. Conclusion: PSQ score is correlated with intraoperative tourniquet pain. In addition, sex and age also affect the time of having intraoperative tourniquet pain. Keywords: Pain Sensitivity Questionnaire, Tourniquet, Ankle surgery, Nerve block, Pain